2014
DOI: 10.1051/0004-6361/201322705
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cosmic rays measured by UVS on Voyager 1 and the end of the modulation

Abstract: The detectors of the Ultraviolet Spectrographs (UVS) on Voyager 1/2 are recording a background intensity that was earlier assigned mainly to disintegrations in the radio-isotope thermoelectric generator and systematically subtracted from the signal to infer photon counting. Here, we show that it arises instead from galactic cosmic rays (GCRs). We show the GCR flux measured by UVS on Voyager 1 from 1992 to August 2013, and by comparing to data from the GCR dedicated detectors, we estimate the energy range respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…The particle background spectrum was measured during dedicated observations and was found to be very stable over the years, with very little channel to channel variation (see supporting information in Lallement et al, ). Lallement et al () have studied in detail the temporal evolution of the Voyager 1 UVS background since 1993. They found that there is a perfect correlation between the UVS background and the Cosmic Ray Subsystem (CRS) signal from energetic particles with energy above 70 MeV (see Figures 1 and 2 in Lallement et al, and Figure a for an illustration).…”
Section: Voyager 1/uvs Observations In 2003–2014mentioning
confidence: 99%
“…The particle background spectrum was measured during dedicated observations and was found to be very stable over the years, with very little channel to channel variation (see supporting information in Lallement et al, ). Lallement et al () have studied in detail the temporal evolution of the Voyager 1 UVS background since 1993. They found that there is a perfect correlation between the UVS background and the Cosmic Ray Subsystem (CRS) signal from energetic particles with energy above 70 MeV (see Figures 1 and 2 in Lallement et al, and Figure a for an illustration).…”
Section: Voyager 1/uvs Observations In 2003–2014mentioning
confidence: 99%
“…While the putative million-degree gas was not seen in the expected extreme-UV emission by the CHIPS satellite (Hurwitz et al 2005) nor in O vi 1032 Å absorption (Cox 2005;Barstow et al 2010), recent works making use of soft X-ray shadows, Planck mm-wavelength data, and Local Bubble maps have now considerably reinforced the idea that there is such hot gas within the cavity (Snowden et al 2015). The picture is complicated by the interaction between the heliosphere and surrounding ISM, such as charge exchange between the solar wind ions and interstellar atoms (e.g., Lallement et al 2014b;Zirnstein et al 2015; but see Galeazzi et al 2014), indicating local "fluff" of a more neutral kind (Frisch 1998). Any novel way or tracer that can be used to map the Local Bubble is therefore highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…These time variable magnetic barriers cause the radial velocity to decrease within this region (Pogorelov et al 2009). Finally, Lallement et al (2014) suggest that, as the flow speed decreases to 10 km s −1 , the charge-exchange rate increases considerably, leading rapid momentum loss and further deceleration in the HS.…”
Section: Introductionmentioning
confidence: 91%
“…The non-conservation of magnetic flux at V1 could be explained if reconnection were taking place within the sector region (Drake et al 2010;Opher et al 2011) since V1 was immersed within this region throughout the HS while V2 went in and out. Lallement et al (2014) also note that in the stagnation region, where a large fraction of the plasma is undergoing charge-exchange, magnetic flux may not be conserved as well.…”
Section: Introductionmentioning
confidence: 99%